2004
DOI: 10.2310/7070.2004.03075
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution X-Ray Computed Tomographic Scanning of the Human Stapes Footplate

Abstract: Objectives: The mechanical behaviour of the footplate and its annular ligament depends critically on their shape and orientation in the oval window, but accurate measurements have been difficult to make owing to their small size. Our aims are to visualize the footplate at high resolution and understand its dynamics. Methods: The human cadaver stapes footplate was dissected, and very high-resolution x-ray computed tomographic (CT) scans, with voxel sizes from 4 to 8 µm, were performed. Locally developed softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Moreover, the AL thickness near point 1 is almost twice as large as the thickness near point 2. This is consistent with the literature (Hagr et al 2004;Ohashi et al 2006;Sim et al 2013). Such an anatomical structure leads to a higher AL stiffness at the SF posterior edge (point 1) than at the anterior edge (point 2).…”
Section: Spring Constant Of the Al Of The Human Stapessupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, the AL thickness near point 1 is almost twice as large as the thickness near point 2. This is consistent with the literature (Hagr et al 2004;Ohashi et al 2006;Sim et al 2013). Such an anatomical structure leads to a higher AL stiffness at the SF posterior edge (point 1) than at the anterior edge (point 2).…”
Section: Spring Constant Of the Al Of The Human Stapessupporting
confidence: 94%
“…The shapes of both the OW niche and the SF are very irregular and vary among individuals (e.g., Hagr et al 2004;Sim et al 2013). Numerous authors have treated the AL as an elliptical ring in finite element modeling of the middle ear (Ladak and Funnell 1996;Sun et al 2002, Gan et al 2011, Gentil et al 2011.…”
Section: Elastic Modulus Of the Al Of The Human Stapesmentioning
confidence: 99%
“…In previous CT-based studies of the ME, the following model resolutions were reported: 5.5 μm on gerbil (Elkhouri et al 2006), 6 μm on human (Hagr et al 2004), 10 μm on cat (Decraemer et al 2003), and 10 μm on human (Vogel 1999). Though these numbers are comparable to our isometric 8.5-μm voxel size for μCT on gerbil bone, our data and models are of much higher quality than those shown in previous work.…”
Section: Resolutionmentioning
confidence: 99%
“…2C depicts the oval window length L3 and width L4. Previous histology on the human middle ear suggests that the SAL is thicker in the anterior than in the posterior [17, 18]. However, due to technique limitation, accurate in vivo measurement along the entire perimeter of the footplate to measure this is not currently possible.…”
Section: Methodsmentioning
confidence: 99%